Literasi Membaca bagi Anak di Lingkungan TPA Desa Huntu Selatan Kabupaten Bone Bolango - Ita Meiarni; Wa Ode Irawati (Komunal Jurnal Pengabdian Masyarakat, 2023)
Literacy can be defined as a complex ability that consists of the ability to read, write, the ability to retrieve and interpret types of texts and the ability of students to think using existing sources of knowledge, both in visual, print and audiovisual forms. Basic literacy skills can be obtained by reading, writing, listening, counting and speaking. In this service, it is specialized in reading literacy with the aim of increasing children's interest in reading. The activities carried out such as the introduction of basic literacy and reading interest; literacy movements in the form of reading children's stories, reading poetry, and reading rhymes; and playing with literacy themes, such as connecting stories and composing words can be used as activities that help foster children's interest in reading in order to support the National Literacy Movement.